PELATIHAN MANAJEMEN KARIR SERTA ETIKA BEKERJA UNTUK MENGEMBANGKAN KEPRIBADIAN DAN MOTIVASI MAHASISWASTIKES BHAKTIALQODIRI JEMBER - FIRDAUS, VERA (Jurnal Terapan Abdimas, 2017)
AbstractPersonality is one of the dominant factors that determine the attitudes and behavior of humans in order to arrange how to relate to others, work together effectively. Career management means for people to be able to plan his careers to improve his status and salary, ensuring the safety of jobs, and retain his competitive value in the labor market. In order to enter the world of work, the students also need to recognize the strategic function of himself, intelligent and has a competitive value. This strategic function must be framed with ethics, personality and devotion. This training is intended to make students of Nursing and Midwifery Academy of Health (STIKES) Bhakti Al Qodiri Jember have a positive mindset about the direction of his career with organizing themselves, arrange the way of thinking and doing management career. The results of the training program is increasing knowledge and understanding of students about career management and ethics work, the students are able to measure his motivation. Appreciation and enthusiasm for the process of ongoing activities, student involvement in the game, as well the interesting dialogue and as the desire for sustainable activity is a measure of the success of this training program. This program is also to establish good cooperation between STIKES Bhakti Al Qodiri and IKIP PGRI Jember which is signed in a Memorandum of Understanding. AbstrakKepribadian merupakan salah satu faktor dominan yang menentukan sikap dan perilaku manusia agar dapat mengatur bagaimana berhubungan dengan orang lain, bekerja sama secara efektif. Manajemen karir dimaksudkan agar individu mampu merencanakan karir sehingga mampu meningkatkan status dan gaji, memastikan keselamatan pekerjaan, dan mempertahan nilai kompetitif dirinya di pasar tenaga kerja. Dalam rangka memasuki dunia kerja, mahasiswa juga perlu mengenali fungsi strategis dirinya, yang cerdas dan memiliki nilai kompetitif. Fungsi strategis ini haruslah dibingkai dengan etika, kepribadian serta ketaqwaan. Pelatihan ini dimaksudkan agar mahasiswa Keperawatan dan Kebidanan Akademi Kesehatan (Stikes) Bhakti Al Qodiri Jember mempunyai mindset positif tentang arah karirnya dengan menata diri, menata cara berfikir dan melakukan manajemen karirnya. Hasil yang diperoleh dari program pelatihan adalah meningkatnya pengetahuan dan pemahaman mahasiswa tentang manajemen karit dan etika bekerja, mahasiswa mampu mengukur motivasi dirinya. Mahasiwa di Akademi Kesehatan (Stikes) Bhakti Al Qodiri Jember sangat apresiatif terhadap pelaksanaan kegiatan pengabdian kepada masyakarat ini. Ini tampak pada antusiasme selama proses kegiatan berlangsung, keterlibatan mahasiswa dalam permainan ini. Serta dialog yang berlangsung sangat menarik. Program ini juga mampu menjalin kerja sama baik antara Stikes Bhakti Al Qodiri Jember dengan IKIP PGRI Jember yang ditandai dengan nota kesepakatan bersama.